Social care for older adults in the criminal justice system: a brief report from a nominal group - O'Neill, Adam (The journal of forensic psychiatry & psychology, 2025)
In line with increasing numbers of older prisoners, demand for social care in prisons is also on the rise. However, social care provision for prisoners appears to be of variable quality and there is minimal research on how best to meet the social care needs of older people in this environment. This paper therefore aims to explore the views of experts involved in prison social care to identify challenges and improve understanding on how best to support prisoners with social care needs. A nominal group was conducted to explore the views of nine participants from private, public, and third sector organisations, including two heads of healthcare, three specialist nurses, an occupational therapist, a consultant forensic psychiatrist, a social care team leader, and a mental health coordinator. Seven key themes emerged: 1) unsuitable environment and regime; 2) varied models of social care; 3) peer support; 4) staff training, collaboration, and understanding; 5) alternative specialised facilities; 6) ‘lower-level’ needs; and 7) issues on release. Overall, these themes mirror findings in the wider literature. However, research is typically focused on male prisons, and is lacking on women. Research on peer support and lower-level social care needs is similarly limited. The findings of this paper can stimulate future research in these directions, as well as informing the national strategy for an ageing prison population, policy, and practice.